Fertilizer placement to maximize nitrogen use by fescue. (20th March 2016) - Raczkowski, Charles W.; Kissel, David E.; Vigil, Merle F.; Cabrera, Miguel L.
ABSTRACT: The method of fertilizer nitrogen (N) application can affect N uptake in tall fescue and therefore its yield and quality. Subsurface-banding (knife) of fertilizer maximizes fescue N uptake in the poorly-drained clay-pan soils of southeastern Kansas. This study was conducted to determine if knifed N results in greater N uptake than the conventional top-dress application method in a deep, well-drained soil of east-central Kansas. The experiment, conducted in a Smolan silty clay loam soil, was a split-plot with fertilizer nitrogen rates 0, 140 and 280 kg N ha −1 applied as urea-ammonium nitrate (UAN, 28% N), knifed or top-dressed. Soil inorganic N [ammonium (NH4 )- and nitrate (NO3 –N)] and N in roots and plant tops were measured at various times during the growing season. At final harvest, most of the knifed N (99.7%) was accounted for in plant tissue (roots and tops) and soil, with more than half of the knifed N remaining as soil inorganic N. With the top-dressed method, 27% was unaccounted for and presumed lost in gaseous form. Knifing fertilizer N in fescue fields of east-central Kansas will maximize the availability of N, reduce potential N losses, and increase forage quality.